Supreme Court of Canada Practice 2025 Edition - Watt, D. Lynne; Beedell, Jeffrey; Ragan, Graham; Estabrooks, Matthew (Carswell Canada, 2025)
Legislation has been updated up to Canada Gazette Vol 159: 19 (September10, 2025)